Forced Abstinence from Cocaine Self-Administration is Associated with DNA Methylation Changes in Myelin Genes in the Corpus Callosum: a Preliminary Study - Nielsen, David A.; Huang, Wen; Hamon, Sara C.; Maili, Lorena; Witkin, Brian M.; Fox, Robert G.; Cunningham, Kathryn A.; Moeller, F. G. (Frontiers in Psychiatry, 2012)
Background: Human cocaine abuse is associated with alterations in white matter integrity revealed upon brain imaging, an observation that is recapitulated in an animal model of continuous cocaine exposure. The mechanism through which cocaine may affect white matter is unknown and the present study tested the hypothesis that cocaine self-administration results in changes in DNA methylation that could result in altered expression of several myelin genes that could contribute to the effects of cocaine on white matter integrity. Methods: In the present study, we examined the impact of forced abstinence from cocaine self-administration on chromatin associated changes in white matter. To this end, rats were trained to self-administer cocaine (0.75 mg/kg/0.1 mL infusion) for 14 days followed by forced abstinence for 1 day (n = 6) or 30 days (n = 6) before sacrifice. Drug-free, sham surgery controls (n = 7) were paired with the experimental groups. Global DNA methylation and DNA methylation at specific CpG sites in the promoter regions ofmyelin basic protein (Mbp), proteolipid protein-1 (Plp1), and SRY-related HMG-box-10 (Sox10) genes were analyzed in DNA extracted from corpus callosum. Results: Significant differences in the overall methylation patterns of the Sox10 promoter region were observed in the corpus callosum of rats at 30 days of forced abstinence from cocaine self-administration relative to sham controls; the −189, −142, −93, and −62 CpG sites were significantly hypomethylated point-wise at this time point. After correction for multiple comparisons, no differences in global methylation or the methylation patterns of Mbp or Plp1 were found. Conclusion: Forced abstinence from cocaine self-administration was associated with differences in DNA methylation at specific CpG sites in the promoter region of the Sox10 gene in corpus callosum. These changes may be related to reductions in normal age related changes in DNA methylation and could be a factor in white matter alterations seen after withdrawal from repeated cocaine self-administration. Further research is warranted examining the effects of cocaine on DNA methylation in white matter.